2018
DOI: 10.3389/fevo.2018.00090
|View full text |Cite
|
Sign up to set email alerts
|

Transient Expression of Whitefly Effectors in Nicotiana benthamiana Leaves Activates Systemic Immunity Against the Leaf Pathogen Pseudomonas syringae and Soil-Borne Pathogen Ralstonia solanacearum

Abstract: Infestation of plants with the phloem-feeding whitefly Bemisia tabaci modulates root microbiota and both local and systemic immunity against microbial pathogens. Specifically, aboveground whitefly infestation suppresses pathogen propagation and symptom development caused by the soil-borne pathogens Agrobacterium tumefaciens and Ralstonia solanacearum in the root system through systemic signal transduction. Therefore, we hypothesized that secreted protein(s)/non-protein factors from whitefly saliva (referred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Tomato plants experiencing different stresses produced exudates that acted as chemoattractants for the beneficial fungus Trichoderma harzianum (Lombardi et al, 2018). Other studies have shown that aphid feeding or whitefly infestation of pepper and tobacco leaves can cause a transcriptional reprogramming in roots and changes in the root microbiome composition which makes plants more resistant to foliar and soilborne pathogens (Yang et al, 2011;Lee et al, 2012;Lee et al, 2018). Recently, Berendsen et al (2018) demonstrated that Arabidopsis leaf infection by the biotrophic oomycete Hyaloperonospora arabidopsidis (Hpa) can lead to the enrichment of three bacterial taxa (Xanthomonas spp., Stenotrophomonas spp., and Microbacterium spp.)…”
Section: "Cry For Help" During Infection Of Plantsmentioning
confidence: 99%
“…Tomato plants experiencing different stresses produced exudates that acted as chemoattractants for the beneficial fungus Trichoderma harzianum (Lombardi et al, 2018). Other studies have shown that aphid feeding or whitefly infestation of pepper and tobacco leaves can cause a transcriptional reprogramming in roots and changes in the root microbiome composition which makes plants more resistant to foliar and soilborne pathogens (Yang et al, 2011;Lee et al, 2012;Lee et al, 2018). Recently, Berendsen et al (2018) demonstrated that Arabidopsis leaf infection by the biotrophic oomycete Hyaloperonospora arabidopsidis (Hpa) can lead to the enrichment of three bacterial taxa (Xanthomonas spp., Stenotrophomonas spp., and Microbacterium spp.)…”
Section: "Cry For Help" During Infection Of Plantsmentioning
confidence: 99%
“…Whitefly, Bemisia tabaci (Hemiptera), is a polyphagous insect and a supervector, transmitting more than 300 plant virus species, that is a threat for many crops across the globe [1]. Whitefly might mediate the suppression of plant defences by secreting protein effectors to improve host colonization and reproductive fitness [6,7]. The whitefly-transmitted monopartite geminivirus begomoviruses are frequently associated with pandemic crop diseases such as tomato yellow leaf curl virus (TYLCV) and tomato yellow leaf curl China virus [8].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary Table 1 depicts articles that have been published on aphid, planthopper and psyllid effectors. To date, six studies describing whitefly effectors have been published (Table 1) (Van Kleeff et al, 2016;Yang et al, 2017;Lee et al, 2018;Su et al, 2019;Wang et al, 2019;Xu et al, 2019). These effectors and their in planta locations and modes of action are illustrated in Figures 1A,B, respectively.…”
Section: Identified Whitefly Effectorsmentioning
confidence: 99%
“…tabaci or P. syringae pv. syringae (Lee et al, 2018). Of the 893 cDNAs tested, three effectors (2G4 and 2G5 encoding proteins with unknown function, and 6A10, a partial transcript of a large subunit ribosomal RNA) were selected using this bioassay.…”
Section: Identified Whitefly Effectorsmentioning
confidence: 99%
See 1 more Smart Citation